2004
DOI: 10.1055/s-2004-820992
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Propofol Infusion Syndrome in Association with Ketogenic Diet

Abstract: Propofol is used for the treatment of refractory status epilepticus. When given as a long-term infusion propofol may cause a rare but frequently fatal complication, the propofol infusion syndrome. The hallmarks are metabolic acidosis, lipemia, rhabdomyolysis and myocardial failure. Propofol infusion syndrome is caused by impaired fatty acid oxidation. Beside anticonvulsants the ketogenic diet, a high-fat, low-carbohydrate, adequate-protein diet, is an effective treatment for difficult-to-control seizures. We r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(53 citation statements)
references
References 11 publications
0
51
0
2
Order By: Relevance
“…A 10-year-old boy suffered fatal propofol infusion syndrome when administered the ketogenic diet [30]. In this patient, propofol was believed to impair fatty acid oxidation, a necessary step in long chain fatty acid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…A 10-year-old boy suffered fatal propofol infusion syndrome when administered the ketogenic diet [30]. In this patient, propofol was believed to impair fatty acid oxidation, a necessary step in long chain fatty acid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In an intensive care unit, KD should be avoided in children receiving propofol infusion due to the risk of fatal propofol infusion syndrome. 29 Over-the-counter medicines may have carbohydrates and can lead to ketosis reversal and seizure breakthroughs. Adequate counseling of the patient's caregiver is necessary.…”
Section: Special Situationsmentioning
confidence: 99%
“…Excess serum fatty-acid concentrations cause ventricular arrhythmias [31,44]. A case report speculated that PRIS was precipitated by the commencement of a ketogenic diet (high fat, low carbohydrate) as adjuvant therapy for refractory status epilepticus in a 10-year-old boy sedated with propofol [11]. It suggested that the fat load, coupled with propofol-mediated impairment of mitochondrial fatty-acid oxidation, caused the metabolic acidosis.…”
Section: Mechanism Of Prismentioning
confidence: 99%